2020
DOI: 10.1017/cts.2020.538
|View full text |Cite
|
Sign up to set email alerts
|

Aligning community-engaged research competencies with online training resources across the Clinical and Translational Science Award Consortium

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…[20][21][22] The reports informing this manuscript indicate that academic institutions have augmented their infrastructure for responding to community issues instead of focusing on individual, isolated research projects. [23][24][25][26][27] Especially now, further transformation is necessary for institutions to develop the capacity to engage communities in all phases of translational science. This aligns with the NCATS Advisory Council Working Group calling for a workforce that is competent in community engagement and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] The reports informing this manuscript indicate that academic institutions have augmented their infrastructure for responding to community issues instead of focusing on individual, isolated research projects. [23][24][25][26][27] Especially now, further transformation is necessary for institutions to develop the capacity to engage communities in all phases of translational science. This aligns with the NCATS Advisory Council Working Group calling for a workforce that is competent in community engagement and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Meaningful, authentic, and equitable community engagement in clinical and translational science is essential to improve the health and wellbeing of communities 47 Our findings are consistent with the literature that highlights the need for training academic researchers on equitable community partnerships 48 . Findings of a systematic review of online CEnR resources from all CTSAs between 2018 and 2019 found that major areas of https://doi.org/10.1017/cts.2021.858 domain address across online resources included CEnR methods and knowledge and relationships with communities 49 . Community stakeholders in our study emphasized the importance of having a critical examination of personal biases due to its potential impact on relationships and the collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…(13) Core competencies should include: 1) social determinants of health and historical injustices; 2) CE principles and community knowledge and relationships; 3) resource sharing and communication; 4) personal traits for successful CE, including cultural humility; 5) elements and value of community-engaged research; 6) program evaluation for CE; and 7) dissemination and advocacy in CE. (11) The importance of sustainability and trustworthiness should be interwoven throughout the curriculum. (2; 26; 41; 42) Some of the existing CE-related educational content(12; 14; 43-45) focus on specific activities or models (e.g., CBPR), (13; 15; 46; 47) and others on service-learning (or critical service-learning), which is the predominant form of pedagogy in academic health institutions.…”
Section: Elements Of Ce Pedagogymentioning
confidence: 99%
“…However, few published pedagogical frameworks exist to guide CE curriculum development across disciplines. There is also marked heterogeneity across existing content and a lack of a shared approach for CE education [11,23].…”
Section: The Need For a Framework For Ce Pedagogymentioning
confidence: 99%
See 1 more Smart Citation